Manajemen dan Kepempimpinan - Etika Pujianti; Irwandi; Iswanto; Junaidi; Lukman Al Faht; Mochamad Nurul Amin; Mohamad Akbar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Management and leadership are two interrelated components that play a crucial role in determining the success of an organization. Management focuses on planning, organizing, implementing, and controlling organizational resources to achieve goals effectively and efficiently, while leadership emphasizes influencing, motivating, and guiding individuals toward achieving shared objectives. This paper aims to analyze the relationship between management and leadership and their contribution to improving organizational performance, particularly in educational institutions. The study employs a library research method by reviewing relevant books, journal articles, and previous studies. The findings indicate that effective management cannot function optimally without strong leadership, and effective leadership requires a well-structured management system to achieve organizational goals sustainably. Therefore, the integration of management and leadership is essential for establishing good governance, fostering innovation, enhancing organizational performance, and improving the quality and competitiveness of educational institutions in the era of globalization and digital transformation.